Shape- and Size-Controlled Preparation of Columnar Layered Transition Metal Hydroxides Enriched with Edges - Watanabe, Akira; Muramatsu, Keisuke; Sugimoto, Wataru (Meeting abstracts (Electrochemical Society), 2024)
Layered transition metal hydroxides have been extensively studied as electrocatalyst for alkaline water electrolysis. 1 The morphological features such as size, aspect ratio, and exposed surface is known to strongly affect the performance of electrocatalysts, and edges are known to particularly exthibit high activity for oxygen evolution reactions. 2 Thus, controlling the crystal growth direction of layered metal hydroxides to expose more edges may be an effective method to enhance the catalytic activity of metal hydroxides. In general, layered materials, including layered metal hydroxides, grow preferentially along the lateral directions to form plate-like crystals, which means that preparation of columnar crystals with an aspect ratio of the thickness to the lateral size higher than 1 is difficult. Recently, we found the formation of columnar layered metal hydroxides with an aspect ratio exceeding 1 by utilizing metal-diamine complexes as precursors. 3 Here, we aim to control the size and aspect ratio of columnar crystals. We focused on the stability of the complexes and evaluated the anisotropic growth behavior of β-Co(OH) 2 . Columnar crystals of metal hydroxide are synthesized by mixing metal salt solution and diamine ligand solution at specific molar ratios, followed by heating under hydrothermal conditions. During hydrothermal treatment, metal ions, which can undergo condensation, are gradually released from metal-diamine complexes, leading to the formation of supersaturated solutions. When the degree of supersaturation is relatively high, anisotropic growth towards the stacking direction occurs. The stability of the complexes becomes a controlling factor for crystal shape. By using cobalt ions as the metal source and N,N' -dimethylethylenediamine ( NN' -dmeda) as the ligand, [ NN' -dmeda]/[Co 2+ ] ratio was varied from 3 to 30 and the morphological change of the products was evaluated. Scanning electron microscopy images show microscale hexagonal-prism shaped crystals with aspect ratios exceeding 1 at [ NN' -dmeda]/[Co 2+ ] ratios of 3, 5, 10, and 15. Powder X-ray diffraction and electron diffraction analysis indicate that all products were β-Co(OH) 2 and the long-axis direction of the columnar crystals corresponded to the stacking direction. Thus, the outer surfaces of these columnar crystals were enriched with edges. In the range of [ NN' -dmeda]/[Co 2+ ] = 3–10, the overall crystal size increased both in the stacking and lateral direction according to the increase of [ NN' -dmeda]/[Co 2+ ] while maintaining an average aspect ratio of approximately 2. At [ NN' -dmeda]/[Co 2+ ] = 15, columnar crystals with smaller aspect ratios were formed, and at [ NN' -dmeda]/[Co 2+ ] = 30, plate-like crystals with lateral sizes of about 20 μm were formed. Because the increase in [ NN' -dmeda]/[Co 2+ ] led to stabilization of metal complex and a decrease in the degree of supersaturation, the decrease in aspect ratio at [ NN' -dmeda]/[Co 2+ ] = 15–30 suggests that high degree of supersaturation is favable for the anisotropic growth. Therefore, controlling the degree of supersaturation by [ NN' -dmeda]/[Co 2+ ] enables the variation of the size and aspect ratio of columnar crystals. References (1) G. Chen, H. Wan, W. Ma, N. Zhang, Y. Cao, X. Liu, J. Wang and R. Ma, Adv. Energy Mater. , 10 , 1902535 (2020). (2) S. Wang, Q. Jiang, S. Ju, C.-S. Hsu, H. M. Chen, D. Zhang and F. Song, Nat. Commun. , 13 , 6650 (2022). (3) K. Muramatsu, M. Jimba, Y. Yamada, H. Wada, A. Shimojima and K. Kuroda, Inorg. Chem. , 61 , 8490 (2022). Figure 1